Classificação arquivística em arquivos universitários: uma análise da aplicação dos procedimentos no contexto dos cursos de Pós-Graduação do Núcleo de Ciências Agrárias e Desenvolvimento Rural - NCADR - COSTA, Raí Rocha (2024)
The Project had as objective analyze and describ the process of applying the Archival Classification in the accumulated documents of Núcleo de Ciências Agrarias e Desenvolvimento Rural (NCADR), as well as the benefits that are a procedure that is part of Records Management can bring to an organization It’s advisable to be universty archives, show some of the reality in this context. Presenting the instrument of classification of the final activity, which is elaborated by CONARQ, as well as the application and verification of the update, the needs of organization, access, understanding and retrieval of information. The research is characterized as a description using the case study method with the qualitative approach. From the results the importance of the correct classification of the archives was realized, concluding that it is a classification and an important procedure for treatment, dissemination and retrieval of the information